MARKETING APPROACHES TO THE FUNCTIONING ENTERPRISES OF EGG POULTRY INDUSTRY OF UKRAINE (INNOVATIVE ECONOMY, 2020)
Varchenko O.M., Havryk O.Yu., Khomiak N.V. MARKETING APPROACHES TO THE FUNCTIONING ENTERPRISES OF EGG POULTRY INDUSTRY OF UKRAINEPurpose. The aim of the article is the development of practical recommendations for increasing the efficiency of marketing activities of egg poultry enterprises.Methodology of research. General scientific and special methods of economic research are used in the paper, in particular: a systematic approach − when studying the connections between phenomena and processes in the system of marketing support of market activity of enterprises; economic and statistical methods − in determining the dynamics, structure and performance of agricultural enterprises; comparative − in assessing the efficiency of activities and comparing levels of enterprise development; settlement and constructive − in developing marketing strategies for agricultural enterprises.Findings. It has been determined that the functioning of Ukrainian poultry enterprises in the target segments of the market for eggs and egg products requires taking into account the fact that the market is constantly developing dynamically. It has been established that in order to adapt to changes in market conditions and to continue the successful operation of an enterprise, it is necessary to take into account numerous factors at all stages of marketing management and to provide a flexible adaptation of the enterprise to their changes. It is revealed that the manifestation of adaptation of enterprises to changes in the factors of the functioning environment are marketing tools, among which the important place is given to product strategies, ensuring product compliance with market requirements, marketing communications, which contribute to the increase in sales.Originality. It has been established that the current market situation is characterized by a high level of competition and market positioning as saturated with increasing export orientation and the emergence of periodic risks of overfishing. It is substantiated that under these conditions, with sufficiently intensive production, the competitive advantages of poultry farms can be formed and maintained exclusively through increased marketing, which requires the adaptation of scientific approaches to the assessment and forecasting of demand, pricing, consumer motivation, and the introduction of marketing strategies. It is revealed that small regional and local egg producers do not observe complex approaches to using a complex of marketing tools.Practical value. The obtained results of the research determine the main directions of the formation of competitive advantages by egg poultry enterprises. Their use will be promoted in practice: introduction of new products (egg production, “bio-eggs”, poultry feed, biogas and organic fertilizers based on chicken manure); activating instruments for the formation of demand and stimulation of product sales; taking into account the changing behavior of consumers, in particular, healthy lifestyle.Key words: marketing environment; enterprise; efficiency; egg poultry farming; egg products.
Keywords: Key words; marketing environment; enterprise; efficiency; egg poultry farming; egg products.